Experimental investigation of variability in bubble departure characteristics between nucleation sites in subcooled boiling flow. (March 2018) - Ooi, Zhiee Jhia; Kumar, Vineet; Bottini, Joseph L.; Brooks, Caleb S.
Highlights: Experimental data of departure diameter and frequency in flow boiling of water. Multiple sites within the same field of view for each condition are analyzed. A normal distribution of bubble departure size is not observed at low pressure. Periodic inactivity of nucleation sites are not captured by current frequency models. Abstract: Experiments have been conducted in a vertical square channel for investigation of wall nucleation characteristics in subcooled boiling flow. Bubble departures from multiple sites are measured simultaneously for nine conditions. Existing bubble departure diameter models are benchmarked and are shown to be satisfactory in predicting condition-average bubble departure diameter. However, significant variations are observed in the bubble departure frequency across different nucleation sites of a given condition largely due to intermittent periods of inactivity. A benchmark of the existing bubble departure frequency models shows that the models are generally applicable to an 'active' frequency but cannot account for the impact of these periods of inactivity. This finding highlights an important issue in the current modeling and understanding of the gas-phase boundary condition. This periodic inactivity, if not incorporated into the wall nucleation modeling, will result in a large overprediction of bubbles generated at the wall. A physical justification for this inactivity is discussed based on the modeling of the active nucleation site density.